THE ANALYSIS OF WORD OF MOUTH (WOM) AND BRAND IMAGE ON PURCHASING DECISIONS - Farida, Nur; Sofi, Muhajir; Susetyorini, Susetyorini (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. A good brand image owned by the company will make it easier for customers to decide on a purchase. Words of mouth (WOM) are positive or negative experiences communicated by someone after buying a product. Research Purpose. This study aims to examine and prove the analysis of Word of Mouth (WOM) and brand image on purchasing decisions. Research Method. This study used quantitative with a case study approach at Harapan Minimarket Tuban Regency, East Java Indonesia. The population was 120 respondents and the number of samples taken was 100 respondents using non-purposive sampling. Data collection was done by using questionnaires. Data analysis used multiple linear regression. Findings. The results showed that a lot of Word of Mouth (WOM) was shown to have a positive and significant influence on increasing purchasing decisions at Harapan Minimarket. Then a quality brand image has a positive and significant effect on purchasing decisions at Harapan Minimarket. Conclusion. Finally, Word of Mouth (WOM) and brand image simultaneously have a positive and significant effect on increasing purchasing decisions at Harapan Minimarket.